Hydrogenation of Maltose in Catalytic Membrane Reactor for Maltitol Production - Makertihartha I.G.B.N.; Khoiruddin; Hakim Ahmad N.; Aryanti P.T.P.; Wenten I.G. (MATEC Web of Conferences, 2018)
Maltitol is one of the low-calorie sweeteners which has a major role in food industries. Due to its characteristics of comparable sweetness level to sucrose, maltitol can be a suitable sugar replacement. In this work, catalytic membrane reactor (CMR) was examined in maltitol production through hydrogenation of maltose. Commercial ceramic membrane impregnated with Kalcat 8030 Nickel was used as the CMR. The reaction was conducted at a batch mode operation, 95 to 110°C of temperature, and 5 to 8 bar of pressure. In the range of working conditions used in this study, up to 47% conversion was achieved. The reaction conversion was significantly affected by temperature and pressure. Results of this preliminary study indicated that CMR can be used for hydrogenation of maltose with good performance under a relatively low operating pressure.